Factors influencing food consumption satisfaction and purchase decisions of restaurant consumers - Maziriri, Eugine Tafadzwa; Rukuni, Tarisai Fritz; Chuchu, Tinashe (Taylor & Francis, 2021)
This research examined how multi-sensory dimensions like sight, sound, and smell would influence customer attitudes toward quick-service restaurants, restaurant patronage intentions, food purchasing decisions, food consumption satisfaction, restaurant attachment, repurchase intention, and positive word of mouth in South African quick-service restaurants. The research embraced a quantitative approach. An online questionnaire was used to collect data from restaurant customers in the Bloemfontein metropolitan. The hypotheses were analysed by applying structural equation modelling. The results uncovered that the study variables were significantly associated and surprisingly, restaurant attachment had a negative and insignificant effect on positive word of mouth. This research adds new fresh knowledge to the established body of knowledge in the context of restaurant food consumption behaviour. This area has little research attention in developing African countries like South Africa.
Keywords: Business; Management and accounting; International business; Marketing; Sound; Sight; Smell; Sensory-dimensions; Food; Purchase-decision; Customer